Fungal Surface and Innate Immune Recognition of Filamentous Fungi - Figueiredo, Rodrigo T.; Carneiro, Leticia A.; Bozza, Marcelo T. (Frontiers in Microbiology, 2011)
The innate immune system performs specific detection of molecules from infectious agents through pattern recognition receptors (PRRs). This recognition triggers inflammatory responses and activation of microbicidal mechanisms by leukocytes. Infections caused by filamentous fungi have increased in incidence and represent an important cause of mortality and morbidity especially in individuals with immunosuppression. This review will discuss the innate immune recognition of filamentous fungi molecules and its importance to infection control and disease.